Exploring English Learning Needs in Bilingual Classes: A Case Study at Universitas Muhammadiyah Makassar - Asrian, Muh; Qalbi, Nur; AM, St. Asmayanti (FKIP Unismuh Makassar, 2025)
This study analyzes the English learning needs of bilingual students in the Faculty of Socio-Politics at Universitas Muhammadiyah Makassar, emphasizing the relevance of English for Specific Purposes (ESP) in higher education. Using a qualitative descriptive method, data were collected from five purposively selected sixth-semester students through interviews and open-ended questionnaires. The findings reveal that students require English proficiency for effective communication in academic and professional contexts, particularly in areas related to daily life, science, technology, and international public administration careers. Speaking, listening, and writing skills were identified as top priorities. The study also found that current teaching materials generally align with students' needs, but lack engagement and contextual depth. This research underscores the urgent need to tailor ESP materials more closely to students’ academic and career goals. It contributes to the field by offering insights into how bilingual programs can better support learners through relevant, need-based English instruction.